Association between air pollution levels and drug sales for asthma and allergy in 63 million people in metropolitan France. (3rd June 2023) - El Homsi, Marwan; Sclison, Stéphane; Huguet, Domitille; Dessimond, Boris; Tanno, Luciana Kase; Prud'homme, Julie; Collette, Augustin; Annesi-Maesano, Isabella
Abstract: Introduction: Air pollution is known to have an impact on respiratory health. However, the assessment of this relationship is far from complete and is rarely extended to the country level. We used drug sales data, both Over-The-Counter (OTC) and prescription drugs, to assess exhaustively the impact of air pollution on asthma and allergy at the national level in France. Methods: The WHO Anatomical Therapeutic Chemical (ATC) classification system was used to describe the distribution of sales of drugs of class R03 (Drugs for obstructive airways diseases, overall for asthma) and R06 (Antihistamines for systemic use). We performed a Quasi-Poisson regression model with a generalized additive model (GAM) to estimate the relationship (Relative Risks and 95% Confidence Interval) between drug sales and air pollutants, that is Particulate Matter with a diameter less than 2.5 micrometers (PM2.5 ) and less than 10 micrometers (PM10 ) and Nitrogen dioxide (NO2 ), as assessed using the high-resolution CHIMERE dispersion model. We designed unadjusted and adjusted single-pollutant models as well as two-pollutant models. Results: PM2.5, PM10, and NO2 were significantly and positively associated with sales of R03 and R06 class drugs, after adjustment for potential confounders. Results were confirmed in the two-pollutant model for PM10 and NO2 but not for PM2.5 . Conclusions: Our study confirms the presence of an association between major air pollutants and the sales of drugs against asthma and allergies. Further studies on larger databases and over several years are necessary to confirm and better understand these results.